2013
DOI: 10.3329/jdmc.v21i1.13233
|View full text |Cite
|
Sign up to set email alerts
|

Major co-morbidities in stroke patients: a hospital based study in Bangladesh

Abstract: DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13233 J. Dhaka Med. Coll. 2012; 21(1): 16-22

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This finding corelate with Haque et al shown smoker were 60% and BA Mondel et al showed 58%. 8,9 In my present study 16% also found tobacco chewing it may contribute to recurrent stroke.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This finding corelate with Haque et al shown smoker were 60% and BA Mondel et al showed 58%. 8,9 In my present study 16% also found tobacco chewing it may contribute to recurrent stroke.…”
Section: Discussionsupporting
confidence: 66%
“…Mondel et al showed most patient between 51-60 yrs of age 23.7%. 9 Hossain AM et al showed most patient between 51-60 yrs 39%. 61-70 years 30%.…”
Section: Discussionmentioning
confidence: 97%
“…Hypertension, DM, ischemic heart disease, dyslipidaemia, hematological disorder and respiratory disorders were significant (p value <0.05) association with neurological problems. All these are common comorbidities for vascular events eg stroke [ 25 ].…”
Section: Discussionmentioning
confidence: 99%